Five years when someone we loved had cancer - Publico, Ally (Christian Advocacy Reaching Everyone (C.A.R.E.) Foundation, 2016)
Arlene Publico was diagnosed with Stage III Nasopharyneal Cancer in July 2011. The doctors told her that unless she undergoes chemotherapy and radiation theraphy everyday for three months, she wourld have only six months left to live. But with much patience and love, the Publico family found a treatment protocol far better than what the doctors suggested and that was hope. That hope for Arlene to get well mtivated them so much to care for her together, even in the most difficult states of her cancer. This diary-style book told from the perspective of Arlene's daughter, Ally, records the memories and hardships the family endured together during the most difficult and most precious five years of their entire lives.